Keanekaragaman Jenis Burung di Taman Wisata Alam (TWA) Camplong, Kecamatan Fatuleu Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Andrys Misa; Ludji Michael Riwu Kaho; Fadlan Pramatana (Wana Lestari, 2024)
This study was conducted to determine the diversity of bird species in the Camplong Nature Park (TWA) area located in Fatuleu District, Kupang Regency, East Nusa Tenggara Province. It has a total area of 696.60 ha. This research was conducted in April – May 2022. The method used in this study is the Point Count method for bird observation and the transect path method is used for vegetation analysis. Data was processed using the Significance Index (INP), Shannon Wiener Diversity Index (H'), Equity Index (E) and Conservation Status Presentation formulas. The results showed that the birds found in TWA Camplong as many as 16 species of birds from 13 families. The calculation of bird species diversity in Camplong Nature Park was calculated using the Shanon Winner index classified as medium with a value of H'= 2.658. The results of data analysis (INP) showed the highest INP at 64.76%, while the lowest INP at 1.12%. In the sapling level category, there are 26 species of plants with the highest INP of 49.76% and the lowest INP of 1.01. There are 20 types of pole level categories with the highest INP of 78.65% while the lowest INP is 2.85%. In the tree category, there are 31 plant species with the highest INP of 38.99% and the lowest INP of 2.45%.